PENGEMBANGAN MEDIA ABEL MEMBARA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA HURUF VOKAL DI SDN GUNUNG PICUNG 05 KABUPATEN BOGOR - Rosa, Eneng; Sabila, Putri; Nurlelah, Siti; Nhasyifa, Rizka Meita; Mukri, Rusdiono (Primer Edukasi Journal, 2026)
Reading ability is an important aspect for students to gain knowledge. The aim of this research is to develop media to improve the ability to read vowels called Abel Membara (Let's Learn to Read with Rara). The research location was at SDN Gunung Picung 05, Bogor Regency with subjects as many as 38 grade 1 students and one class teacher. The type of research is Research and Development with the ADDIE model (analysis, design, development, implementation, evaluation). Data was obtained through observation, interviews and questionnaires which were analyzed descriptively. At the analysis stage, interviews were conducted with first grade teachers and data was obtained that students preferred videos with interesting images in learning. The next stage was designing Abel Membara media using the Canva application. The next stage of media development involves material experts and media experts as validators to assess the suitability of the media through a questionnaire. The results of the material expert's validation score were 96.5% and the media expert's 100%, which shows that the Abel Membara media is very suitable for use. The finished media was implemented in trials in the classroom, the results of which were proven to be effective in improving the ability to read vowels. The final stage is evaluation in the form of feedback from teachers and students which shows that this media has great potential to be applied in early literacy learning in elementary schools.